2006
DOI: 10.1016/j.ydbio.2006.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Neogenin interacts with RGMa and Netrin-1 to guide axons within the embryonic vertebrate forebrain

Abstract: In the embryonic forebrain, pioneer axons establish a simple topography of dorsoventral and longitudinal tracts. The cues used by these axons during the initial formation of the axon scaffold remain largely unknown. We have investigated the axon guidance role of Neogenin, a member of the immunoglobulin (Ig) superfamily that binds to the chemoattractive ligand Netrin-1, as well as to the chemorepulsive ligand repulsive guidance molecule (RGMa). Here, we show strong expression of Neogenin and both of its putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
80
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 39 publications
2
80
1
Order By: Relevance
“…Netrin-1 binding to DCC induces chemo-attraction (Keino-Masu et al, 1996), but this response is turned into repulsion if another receptor, uncoordinated-5 (UNC5) co-exists with DCC (Colamarino and Tessier-Lavigne, 1995). Other known netrin-1 receptors that assist in axon guidance are DSCAM (Ly et al, 2008; Andrews et al, 2008; Liu et al, 2009) and Neogenin (Wilson and Key, 2006). More receptors are expected to be involved including membrane-bound proteoglycans (Rajasekharan and Kennedy, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Netrin-1 binding to DCC induces chemo-attraction (Keino-Masu et al, 1996), but this response is turned into repulsion if another receptor, uncoordinated-5 (UNC5) co-exists with DCC (Colamarino and Tessier-Lavigne, 1995). Other known netrin-1 receptors that assist in axon guidance are DSCAM (Ly et al, 2008; Andrews et al, 2008; Liu et al, 2009) and Neogenin (Wilson and Key, 2006). More receptors are expected to be involved including membrane-bound proteoglycans (Rajasekharan and Kennedy, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Neogenin-1 is present in tissues where active growth takes place, and overexpression of neogenin-1 has been observed in a wide variety of human cancers including those of the breast, pancreas, cervix, colon, medulloblastoma and rectum [17-19]. Previous studies have also shown that neogenin-1 may promote cell migration and cell-cell adhesion in human vascular smooth muscle in addition to zebrafish neurectoderm [9, 20]. Also, neogenin-1 is involved in various aspects of cancer progression and metastasis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Neogenin is a membrane protein and widely expressed in most tissues, including liver and skeletal muscle (30 -34). The interactions of neogenin with RGMa and netrins are essential for neural development (35,36). Our previous study showed that the interaction with neogenin is required for HJV release from muscle cells (20).…”
mentioning
confidence: 99%